Steady Laminar Second Grade Fluid Flow Between Two Rotating Porous Discs with Moderate Rotation - verma, P. D.; Sharma, P. R. (Defence Science Journal, 2013)
The flow of a second grade fluid between two rotating porous discs is investigated. The equations of motion are solved by & regular perturbation technique for small cross-flow Reynolds number. The effects of viscoelastic parameter-a, suction/injectidh parameter-R and rotation parameter-b on the velocity components, pressure distribution and skin friction have been discussed numerically and the results a re- compared to those of a Newtonian fluid case.